Mall city : Hong Kong's dreamworlds of consumption - Al, Stefan (University of Hawaiʻi Press, 2016)
Hong Kong is the twenty-first-century paradigmatic capital of consumerism. Of all places, it has the densest and tallest concentration of malls, reaching tens of stories. Hong Kong's malls are also the most visited, sandwiched between subways and skyscrapers. These mall complexes have become cities in and of themselves, accommodating tens of thousands of people who live, work, and play within a single structure. Mall City features Hong Kong as a unique rendering of an advanced consumer society. Retail space has come a long way since the nineteenth-century covered passages of Paris, which once awed the bourgeoisie with glass roofs and gaslights. It has morphed from the arcade to the department store, and from the mall into the "mall city"--Where "expresscalators" crisscross mesmerizing atriums. Highlighting the effects of this development in Hong Kong, this book raises questions about architecture, city planning, culture, and urban life.